2011
DOI: 10.1002/hbm.21433
|View full text |Cite
|
Sign up to set email alerts
|

Near and far space: Understanding the neural mechanisms of spatial attention

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 89 publications
(150 reference statements)
4
39
3
Order By: Relevance
“…The role of rPPC in processing near space is in accordance with previous research (Bjoertomt et al, 2002;Halligan & Marshall, 1991;Lane et al, 2013;Mennemeier et al, 1992;Weiss et al, 2000), as is its relationship with egocentric processing (Committeri et al, 2004;Galati et al, 2000;Hillis et al, 2005;Medina et al, 2009;Neggers et al, 2006;Vallar et al, 1999). Neuropsychological research has indicated that the right hemisphere is involved in egocentric processing in near space (Iachini, Ruggiero, Conson & Trojano, 2013), although this finding was based on extensive fronto-parietal lesions in only four patients making it difficult to determine the precise brain area underlying their impairment .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The role of rPPC in processing near space is in accordance with previous research (Bjoertomt et al, 2002;Halligan & Marshall, 1991;Lane et al, 2013;Mennemeier et al, 1992;Weiss et al, 2000), as is its relationship with egocentric processing (Committeri et al, 2004;Galati et al, 2000;Hillis et al, 2005;Medina et al, 2009;Neggers et al, 2006;Vallar et al, 1999). Neuropsychological research has indicated that the right hemisphere is involved in egocentric processing in near space (Iachini, Ruggiero, Conson & Trojano, 2013), although this finding was based on extensive fronto-parietal lesions in only four patients making it difficult to determine the precise brain area underlying their impairment .…”
Section: Discussionsupporting
confidence: 88%
“…Our previous work (Lane et al, 2013) supported the finding that rVO of the ventral stream is involved in far space processing but not near (Bjoertomt et al, 2002;Butler, Eskes & Vandorpe, 2004;Halligan & Marshall, 1991;Mennemeier et al, 1992;Shelton, Bowers & Heilman, 1990;Valdés-Conroy, Sebastián, Hinojosa, Romá & Santaniello, 2014;Vuilleumier et al, 1998;Weiss et al, 2000). Specifically, 16 Bjoertomt et al (2002) revealed a significant involvement of rVO in a landmark task in far space, which could be identified as an allocentric task albeit not involving visual search.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations